Mapping and Analysing Suicide Locations of Lalitpur, Nepal (Journal on Geoinformatics, Nepal, 2024)
This research utilizes geospatial and statistical analysis to examine spatial patterns in suicide occurrences within the Lalitpur district of Nepal. The dataset comprises suicide locations collected from the Lalitpur Police Range (LPR) over a period of six fiscal years spanning from 2074/75 to 2078/79 (2017 AD to 2023 AD). Textual data undergo preprocessing and geocoding processes to derive locations for spatial analysis. The methodology employs Local Moran's I to identify spatial patterns and Getis Ord Gi* to identify hotspots and coldspots of suicide incidents. Due to location approximations, spatial analyses are conducted at aggregated levels, including administrative units (wards level) and 1km x 1km grids. The study reports the identified hotspots and coldspots based on these analyses.